The EU-MODEX Blended Full-Scale Exercise: A Review. (November 2022) - Carbini, Federico; Angeli, Valentina; Bortolin, Michelangelo; Merlo, Federico; Ragazzoni, Luca
Abstract : Background/Introduction: Amidst the COVID-19 pandemic, the EU-MODEX exercise had to rethink its logistics in order to promote safer environments for its participants. 1 Objectives: To describe the Blended EU-MODEX exercise as a method to minimize the risk of COVID-19 contagion and the role of CRIMEDIM during such innovative approach. Method/Description: The first post-COVID-19 EU-MODEX exercise was performed in October 2021. To avoid travels, three EMTs from Austria, Romania, and Estonia virtually deployed in a fictious country hit by a typhoon, operated independently in their own country. The Excon worked remotely from Germany. The interoperability among the EMTs was simulated using an online tool. When a patient, simulated by a local role player, needed a transfer from the EMT1 in Romania or Austria, all clinical information were shared online and a new role player was prepared with that information to continue the simulation in Estonia. CRIMEDIM personnel located at each EMT were tasked to ensure the consistency and the quality of all the clinical cases, matching the clinical information of the incoming patient with the new role player, especially regarding the treatment received and the makeup instruction. Results/Outcomes: During the exercise, 425 clinical cases were played by the three EMTs. The exercise lasted for 60 hours and provided unique challenges due to its blended nature. No COVID-19 outbreaks were registered following the exercise. Conclusion: The experience of the Blended EU-MODEX exercise showed the potentiality of the virtual simulation environment as an effective alternative to avoid secondary contagion as well as reduce costs.